Performance study of energy conversion system for ocean thermal profiler - Chen, Yanhu; Chen, Bingzhe; He, Meiling; Zhang, Luning; Xia, Qingchao; Yang, Canjun (Frontiers in Marine Science, 2022)
With the increasing scarcity of energy in the world, energy has become an important part of restricting the development and application of traditional ocean profilers. The method of converting ocean thermal energy (OTE) into electrical energy through an energy conversion system is a solution. The model establishment and performance analysis of the energy conversion system are the basis of the ocean thermal profiler (OTP) design. The model and performance are affected by the coupling of multiple parameters, especially rotational speed and pressure. In this study, a universal parameterized model for multi-parameter coupling was proposed. System performance analysis based on experiments including load current, speed, mechanical efficiency and total efficiency was presented. After model parameter identification, the error of mechanical efficiency was within 5%; the total efficiency error was less than 12.8%, and the maximum efficiency point error didn’t exceed 2.21%. The results indicated that the parameterized model was satisfactory for the engineering applications and could guide the design of OTP.